Monetary policy in a low interest rate environment: Reversal rate and risk-taking - Florian Heider; Agnese Leonello (European Central Bank (ECB), 2021)
Using new quarterly narrative evidence, this paper examines the macroeconomic impact of reforms of unemployment benefits (UB) and employment protection legislation (EPL) in the euro area from a Bayesian narrative panel VAR. The approach complements existing micro-econometric evidence by aligning short- and mediumterm effects in a unified framework and assessing state dependencies. Liberalising reforms result in temporary wage declines and highly persistent increases in economic activity and employment. In contrast to UB reforms, the effects of EPL reforms on employment emerge only gradually.This paper develops a simple analytical framework to study the impact of central bank policy-rate changes on banks' credit supply and risk-taking incentives. Unobservable expost bank monitoring of loans creates an external-financing constraint, which determines bank leverage. Unobservable, costly ex-ante screening of borrowers determines the level of bank risk-taking. More risk-taking tightens the external-financing constraint. The policy rate affects the external-financing constraint because it affects both the return on outside investors' alternative investments and loan rates. In a low rate environment, a policy-rate cut reduces bank funding costs less because of a zero lower bound (ZLB) on retail deposit rates. Bank risk-taking is a necessary but not sufficient for a policy-rate cut to become contractionary ("reversal"). Reversal can occur even though banks' net-interest margins increase. Credit market competition plays an important role for the interplay of monetary policy and financing s tability. When banks have market power, a policy-rate cut can increase lending and still lead to risk-taking. We use our analytical framework to discuss the literature on how monetary policy affects the credit supply of banks, with special emphasis on low and negative rates.
Keywords: E44; E52; E58; G20; G21; 330; deposits; zero-lower bound; bank lending; equity multiplier